Trajectories of psychological states of women elite fencers during the final stages of international matches - Doron, J.; Martinent, G. (Journal of Sports Sciences, 2016)
This study examined the trajectories and within-person synergies of psychological processes during the final stages of matches. A process-oriented approach was used with nine women elite fencers during an international competition. Multiple assessments of perceived control, threat and challenge appraisals, problem- and emotion-focused coping, positive and negative affects were completed after each touches using video recall method. Multilevel growth curve analyses (MGCAs) indicated that winning and losing matches were each characterised by distinct psychological processes. Specifically, perceived control, challenge appraisal, problem- and emotion-focused coping, and positive affects increased linearly and threat appraisal decreased linearly for wining matches, whereas negative affects increased linearly for losing matches. Regarding the within-person synergies of psychological processes, MGCAs indicated that (1) perceived control and challenge appraisal were significantly associated with problem- and emotion-focused coping for losing matches, the strength of these associations remaining consistent across touches; (2) problem-focused coping was significantly associated with negative affects whereas emotion-focused coping was significantly associated with positive affects for winning matches, the strength of these associations remaining consistent across touches; and (3) problem- and emotion-focused coping were significantly associated with negative affects for losing matches, the linear trajectory of negative affects accelerating at times when athletes had higher levels of emotion-focused coping. Overall, this study provided insights into transactional processes during competition.